2009
DOI: 10.1186/1476-8518-7-5
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 neutralization by monoclonal antibody against conserved region 2 and patterns of epitope exposure on the surface of native viruses

Abstract: Background: Conserved neutralizing epitopes are considered to be a key role for eliciting broadly neutralizing antibody (NAb). Previously, two conserved neutralizing epitopes of HIV-1 CRF01_AE envelope were identified at amino acid 93-112 of the C1 (C1E) and at 218-239 of the C2 (C2E) regions. To access the potency of antibody directed against conserved epitopes, a monoclonal antibody (MAb) specific to the C2E region was developed and characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…To overcome this problem, diagnostic methods employing shorter HIV antigens were developed. Empirical methods to identify peptides corresponding to unique and highly conserved epitopes of the HIV viruses have been identified that helped in pinpointing amino acid sequences that are more likely to be exposed on the surface of native proteins (Sreepian et al, 2009;Nyambi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this problem, diagnostic methods employing shorter HIV antigens were developed. Empirical methods to identify peptides corresponding to unique and highly conserved epitopes of the HIV viruses have been identified that helped in pinpointing amino acid sequences that are more likely to be exposed on the surface of native proteins (Sreepian et al, 2009;Nyambi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Together with the fact that the C1 region is known to be less variable [ 43 ], the C1 epitopes are interesting targets for neutralizing antibodies. Previously, a report by Sreepian et al , described the presence of antibodies against the C1 region in a subtype CRF01_AE infected HIV-1 individual, however, immunization studies performed with C1 epitopes did not result in neutralizing antibodies [ 44 , 45 ]. The role of the C1 antibodies in the neutralization capacity of ITM4 should be further analyzed.…”
Section: Discussionmentioning
confidence: 99%